Rational Design of Synergistic Structure Between Single-Atoms and Nanoparticles for CO2 Hydrogenation to Formate Under Ambient Conditions - Zhai, Shengliang; Zhang, Ling; Sun, Jikai; Sun, Lei; Jiang, Shuchao; Yu, Tie; Zhai, Dong; Liu, Chengcheng; Li, Zhen; Ren, Guoqing (Frontiers in Chemistry, 2022)
Single-atom catalysts (SACs) as the new frontier in heterogeneous catalysis have attracted increasing attentions. However, rational design of SACs with high catalytic activities for specified reactions still remains challenging. Herein, we report the rational design of a Pd1-PdNPs synergistic structure on 2,6-pyridinedicarbonitrile derived covalent triazine framework (CTFs) as an efficient active site for CO2 hydrogenation to formate under ambient conditions. Compared with the catalysts mainly composed of Pd1 and PdNPs, this hybrid catalyst presented significantly improved catalytic activity. By regulating the ratio of Pd1 to PdNPs, we obtained the optimal catalytic activity with a formate formation rate of 3.66 molHCOOM·molPd-1·h-1 under ambient condition (30 °C, 0.1 MPa). Moreover, as a heterogeneous catalyst, this hybrid catalyst is easily recovered and exhibits about 20% decrease of the catalytic activity after five cycles. These findings are significant in elucidating new rational design principles for CO2 hydrogenation catalysts with superior activity and may open up the possibilities of converting CO2 under ambient conditions.